Left Ventricular Endocardial Dysfunction in Patients with Preserved Ejection Fraction after Receiving Anthracycline. Issue 7 (20th December 2013) - Miyoshi, Tatsuya; Tanaka, Hidekazu; Kaneko, Akihiro; Tatsumi, Kazuhiro; Matsumoto, Kensuke; Minami, Hironobu; Kawai, Hiroya; Hirata, Ken‐ichi
<x xml:space="preserve">Abstract</x> Background Anthracycline chemotherapy generates progressive dose‐dependent left ventricular (LV) dysfunction associated with a poor prognosis. Early detection of minor LV myocardial dysfunction caused by the cardiotoxicity of anthracycline is thus important for predicting global LV dysfunction. Methods Fifty patients with preserved ejection fraction (all ≥55%) after receiving anthracycline chemotherapy were recruited for this study. Two‐dimensional speckle tracking was used to assess global radial and circumferential strains from mid‐LV short‐axis views and global longitudinal strain from the apical four‐ and two‐chamber view as peak global strain curves. Three‐dimensional (3D) radial, circumferential, and longitudinal myocardial function was quantified as a peak global strain curve using 3D speckle tracking from all 16 LV segments. 3D speckle tracking imaging was used to evaluate LV endocardial area change ratio (area strain) quantified as peak global area strain curve (3D‐GAS) to determine LV endocardial function. Twenty age‐, gender‐, and EF‐matched normal volunteers were studied for comparisons. Results Only 3D‐GAS and peak 3D global circumferential strains of the anthracycline group were significantly worse than those of the control group (−43.3 ± 3.1 vs. −45.8 ± 4.3% and −31.6 ± 3.5% vs. −34.4 ± 4.2%, respectively; P = 0.008, P = 0.004) even though global LV systolic and diastolic functions were similar. 3D‐GAS correlated significantly with the cumulative doxorubicin dose (r = 0.316, P = 0.026). It was noteworthy that multivariate analysis showed only 3D‐GAS (β = 0.323, P = 0.025) was independently associated with cumulative doxorubicin dose. Conclusions Three‐dimensional speckle tracking area strain was found useful for early detection of minor LV endocardial dysfunction associated with the use of anthracycline, and may thus prove to be clinically useful for predicting global LV dysfunction.